Education Concept by Rasulullah Shallallahu' Alaihi Wasallam: Analysis of the Hadith Analysis of the Book of Science of Sahih Bukhari - Rohma tin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
This thesis aims to examine the concept of education according to the Prophet Shallallahu ‘Alaihi Wasallam in the book of science, hadith Sahih al-Bukhari. This research needs to be carried out, with the hope of adopting the educational concept adopted by Rasulullah Shallallahu ‘Alaihi Wasallam for education in Indonesia, considering education in Indonesia is only good from the theoretical side, but in practice it is still far from the educational goals which have been formulated by the government. The large of the education budget has not been able to be a solution to the complexity of the education problem. In addition, there are still many misconceptions about the duties and responsibilities of educators, especially educators in Islamic education.This research uses the method of library research, because the object of study is the literary work in the form of a book of hadith, namely Sahih al-Bukhari by Muhammad ibn Isma'il al-Bukhari, specifically in the hadiths which are in the book of science. Therefore, the data needed is textual data, in the form of hadiths about the concept of education according to the Prophet Shallallahu ‘Alaihi Wasallam, the character of educators and the character of students with the interpretation of hadiths from the hadith scholars. The approach method is inductive approach in this research.The final result of this research is, the Sahih al-Bukhari hadith contains an ideal educational concept which has been practiced by the Prophet Shallallahu ‘Alaihi Wasallam, including about the method of education, such as: the question and answer method, the amtsal method, the method of demonstration, the method of discussion, writing methods and memorization methods, also about management and evaluation in Islamic education, the character of educators and students. Thus the concepts of education which have been practiced by Rasulullah Shallallahu ‘Alaihi Wasallam can be applied in Indonesia for the success of the educational goals which have been formulated by the Government. Keywords: the concept of education, the Messenger of Allah, the hadith of science